Analysis of dissolution profiles of iron, zinc, and manganese from complex dietary supplements by ion chromatography and chemometrics. Issue 1 (2nd January 2016) - Blicharska, Eliza; Szczęsna, Barbara; Kocjan, Ryszard; Gumieniczek, Anna; Komsta, Łukasz
ABSTRACT: Four commercially available formulations containing iron, zinc, and manganese were subjected to dissolution profile testing during 60 min and the dissolution was analyzed by ion chromatography. The obtained curves were analyzed directly by principal component analysis (PCA). The main trend (87.1% of variance) was connected with average dissolution percentage over the investigated time. The second component (11.2% of variance) is connected with shape of dissolution profile. All metals behave in the similar way and the differences were connected with excipients. An additional fit was completed on 12 kinetic models: first order kinetics (4 variants), Higuchi (2 variants), Hixson-Crowell (2 variants), Korsemeyer-Peppas, Logistic (2 variants), Peppas-Sahlin, Quadratic (2 variants), Weibull (3 variants), and Zero order kinetics (2 variants). The ranking of the fitting was performed by Akaike information criteria (AIC) values with additional PCA analysis on them, an approach presented in literature for the first time. The main trend (67.4% of variance) was connected with average fit. The second (14.8% of variance) is connected with differences of fitting ability to investigated dissolution curves. This methodology brought an overall look to trends and variances inside obtained data, both the profile shape and fitting ability to particular models. GRAPHICAL ABSTRACT: